IDENTIFIKASI ETNOBOTANI TANAMAN OBAT YANG DIMANFAATKAN OLEH MASYARAKAT KECAMATAN SEMPOR KABUPATEN KEBUMEN - Tri Cahyani Widiastuti; Naelaz Zukhruf Wakhidatul Kiromah; L Ledianasari (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Indonesian is a tropical country that has been known as a producer of various agricultural commodities, including medicinal plants. Traditional medicine is a hereditary heritage of the ancestors who are deeply rooted in the culture of the nation, therefore both in the herb and in its use as a traditional medicine is still based on experiences passed down from generation to generation both orally and in writing. Health services in Indonesia have grown, but people's interest in utilizing traditional medicine remains high. This study aims to reveal the knowledge of the community about the types of plants that are utilized for the fulfillment of daily living needs. This research was conducted around Sempor District Kebumen District. This study uses survey method designed to obtain a description of the various types of medicinal plants used by the community. Determination of informants by using snowball sampling. The results of the survey and the interviews were made of the categories of plant utilization. From the results of the research, it is found that the people around Sempor still have a good knowledge about the diversity of plants and their utilization in everyday life. Based on the survey results, there were 200 species of plants utilized by the community, grouped into categories: foodstuff (90 species), herbal medicine and traditional medicine (44 species), building materials (29 species), fuelwood (13 species) , animal feed ingredients (11 species), craft materials and tools (8 types), fiber materials and rope (3 types), and toxic materials (2 types)